Naive Malerei : Sammlung Burg Lissingen. (Koblenz : Mittelrhein-Museum, 1990)
Ellis, Vivian ; Enulat, Minna ; Gawlowa, Katrzyna ; Generalic, Ivan ; Grams, Erich ; Hagoort, Pieter ; Hansche, Werner ; Heber, Natan ; etc.
Naive Malerei : Sammlung Burg Lissingen, Mittelrhein-Museum, Koblenz, 15. Dezember 1990 - 3. Februar 1991
boek